2017
DOI: 10.1007/s10493-017-0171-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured cinnamon oil has the potential to control Rhipicephalus microplus ticks on cattle

Abstract: The aim of this study was to evaluate the capacity of pure and nanostructured cinnamon oil to control the infestation and reproductive efficiency of Rhipicephalus microplus on dairy cows. In vitro (stage I)-engorged female ticks were immersed in concentrations of 1.0, 5.0 and 10% of cinnamon oil on its pure form, and 0.5, 1.0, and 5.0% of the nanostructured form. 10% cinnamon oil (pure form) showed 100% efficacy, whereas concentrations of 1 and 5% were 62 and 97% efficacious, respectively. Nanocapsules and nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Recently, nanocapsules and nanoemulsions containing cinnamon oil showed high efficacy against engorged female of R. ( B. ) microplus 14 , 15 . Also, Boito et al 16 reported that nanoparticles containing oil of the tea tree interfered in the reproduction of R. ( B. )…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanocapsules and nanoemulsions containing cinnamon oil showed high efficacy against engorged female of R. ( B. ) microplus 14 , 15 . Also, Boito et al 16 reported that nanoparticles containing oil of the tea tree interfered in the reproduction of R. ( B. )…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, other study made by Monteiro et al [51] showed that the non-emulsioned EO did not caused oviposition inhibition. Moreover, after 20 days, the cows that were previously infested and treated with the nanoemulsion were free of the parasites [49]. Similar work done by Galli et al [50] and contributors with Eucalyptus globulus nanoemulsion showed that the formulations at 1% and 5% inhibited parasite reproduction by 50% and 61.2%, respectively.…”
Section: Biological Activities Of Essential Oil Nanoemulsionsmentioning
confidence: 77%
“…Some groups of researchers have reported the acaricidal activity of EO nanoemulsions against this species. Santos et al [49] demonstrated the activity of the nanoemulsion-based in 5% Cinnamomum verum EO that caused 97% and 63.5% of oviposition inhibition, in vitro and in vivo, respectively. In comparison, other study made by Monteiro et al [51] showed that the non-emulsioned EO did not caused oviposition inhibition.…”
Section: Biological Activities Of Essential Oil Nanoemulsionsmentioning
confidence: 99%
“…The insecticidal action of C. zeylanicum oil was also evaluated [8], who showed that the oil controlled Sitophilus zeamais (Coleoptera: Curculionidae), insects that are resistant to traditional insecticides and nevertheless use physiological and behavioral mechanisms to inhibit activity of the oil. The versatility of C. zeylanicum oil have been demonstrated in the literature, where it has been shown to work as an acaricide, and a fungicide, in addition to its insecticidal effect [4,17,18,21].…”
Section: Discussionmentioning
confidence: 98%